Developmental regulation of transcription of whiE, a locus specifying the polyketide spore pigment in Streptomyces coelicolor A3(2) - Kelemen, Gabriella H.; Brian, Paul; Flärdh, Klas; Chamberlin, Leony; Chater, Keith F.; Buttner, Mark J. (Journal of Bacteriology, 1998)
whiE is a complex locus that specifies the polyketide spore pigment in Streptomyces coelicolor A3(2). Two divergently oriented promoters, whiEP1 and whiEP2, were identified in the whiE gene cluster, and their activities were analyzed during colony development in wild-type and sporulation-deficient strains. Both promoters were developmentally regulated; whiEP1 and whiEP2 transcripts were detected transiently at approximately the time when sporulation septa were observed in the aerial hyphae, and transcription from both promoters depended on each of the six known 'early' whi genes required for sporulation septum formation (whiA, -B, -G, -H, -I, and -J). Mutation of the late sporulation-specific sigma factor gene, sigF, had no effect on the activity of whiEPl but blocked transcription from whiEP2. However, σ(F)- containing holoenzyme was not sufficient to direct transcription of whiEP2 in vitro. The whiEP2 promoter controls expression of whiE ORFVIII, encoding a putative flavin adenine dinucleotide-dependent hydroxylase that catalyzes a late tailoring step in the spore pigment biosynthetic pathway. Disruption of whiE ORFVIII causes a change in spore color, from grey to greenish (T.-W. Yu and D. A. Hopwood, Microbiology 141:2779-2791, 1995). Consistent with these observations, construction of a sigF null mutant of S. coelicolor M145 caused the same change in spore color, showing that disruption of sigF in S. coelicolor changes the nature of the spore pigment rather than preventing its synthesis altogether.